Negative pole piece, battery and electric equipment

By introducing liquid-absorbing particles into the negative electrode, and utilizing the melting of the outer shell during overcharging to expose the liquid-absorbing core layer to absorb electrolyte, the safety performance problem of the battery under overcharge conditions is solved. This achieves rapid attainment of the charging cutoff voltage and reduces heat generation, thereby improving the battery's safety and cycle stability.

CN119447163APending Publication Date: 2025-02-14XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411650062.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing batteries have poor safety performance under overcharge conditions and are prone to thermal runaway. Improving safety performance may affect electrochemical performance or be too costly.

Method used

Design a negative electrode sheet containing liquid-absorbing particles. The liquid-absorbing particles consist of a liquid-absorbing core layer and a shell. Under normal operating conditions, the shell isolates the liquid-absorbing core layer from the electrolyte. When overcharged, the shell melts and exposes the liquid-absorbing core layer to absorb the electrolyte, increasing the internal resistance, quickly reaching the charging cutoff voltage, and reducing heat generation.

Benefits of technology

Under overcharge conditions, the absorbent particles effectively consume the electrolyte, reduce side reactions, decrease heat generation, improve battery safety and cycle performance, and prevent thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447163A_ABST
    Figure CN119447163A_ABST
Patent Text Reader

Abstract

The invention relates to a negative pole piece, a battery and electric equipment. The negative electrode piece comprises a negative electrode current collector layer and a negative electrode material layer, the negative electrode current collector layer and the negative electrode material layer are arranged in a stacked mode, the negative electrode material layer comprises liquid absorption particles, each liquid absorption particle comprises a liquid absorption core layer and a shell, the shell wraps the periphery of the liquid absorption core layer, the shell is a polymer shell layer, and the liquid absorption core layer and the shell are arranged in a staggered mode. And the melting temperature T of the shell is more than or equal to 100 DEG C and less than or equal to 150 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode plate, a battery and an electrical device. Background Art

[0002] With the continuous development of battery technology, it is particularly necessary to conduct overcharge tests on batteries to ensure the safety performance of batteries. The battery generates severe heat during overcharge, which will induce side reactions inside the battery. If the battery's overcharge performance is poor, thermal runaway may occur. Therefore, it is particularly important to improve the safety performance of batteries in overcharge conditions. Summary of the invention

[0003] In view of this, the present application provides a negative electrode plate, a battery and an electrical device, wherein the liquid absorbing particles of the negative electrode plate have a good liquid absorbing function when the battery is in an overcharged state, so that the battery has good safety performance in the overcharged state.

[0004] The present application provides a negative electrode plate, which includes: a negative electrode collector layer and a negative electrode material layer, the negative electrode collector layer and the negative electrode material layer are stacked, the negative electrode material layer includes liquid-absorbing particles, the liquid-absorbing particles include a liquid-absorbing core layer and a shell, the shell is coated on the periphery of the liquid-absorbing core layer, the shell is a polymer shell layer, and the melting temperature T of the shell is in the range of: 100°C≤T≤150°C.

[0005] Furthermore, the range of the electrical conductivity σ of the shell is: 10 -12 S / m≤σ≤10 -9 S / m.

[0006] Furthermore, the range of the liquid absorption amount Q of the liquid absorbing particles per unit mass is: 3 mL / g≤Q≤7 mL / g.

[0007] Furthermore, the range of the median particle size d1 of the liquid absorbing core layer is: 10nm≤d1≤500nm.

[0008] Furthermore, the specific surface area S of the liquid absorbing core layer is in the range of: 1.1 m 2 / g≤S≤1.7m 2 / g.

[0009] Furthermore, the thickness of the shell is h, and the median particle size of the liquid-absorbing particles is d2, then the relationship is satisfied: 0.3≤h / d2≤0.5.

[0010] Furthermore, the thickness h of the shell is in the range of 20nm≤h≤300nm.

[0011] Furthermore, the range of the median particle size d2 of the liquid absorbing particles is: 20nm≤d2≤1000nm.

[0012] Furthermore, in the negative electrode material layer, the mass fraction a of the liquid absorbing particles is in the range of 0.1%≤a≤0.5%.

[0013] Furthermore, the liquid absorbing core layer comprises a silicon-based material, and the silicon-based material comprises at least one of silicon dioxide, silicon, silicon carbide, and sodium silicate.

[0014] Furthermore, the material of the shell is selected from at least one of polyethylene, polyacrylic acid, polyimide, polyester, polyvinyl chloride, polyethylene terephthalate and polybutylene succinate.

[0015] The present application also provides a battery, which includes: a negative electrode plate, a diaphragm, a positive electrode plate and an electrolyte provided in the present application, wherein the diaphragm is arranged on one side of the negative electrode plate; the positive electrode plate is arranged on the side of the diaphragm away from the negative electrode plate; the electrolyte is used to infiltrate at least a portion of the negative electrode plate, the diaphragm and the positive electrode plate.

[0016] The present application also provides an electrical device, which includes: a device body and a battery provided in the present application, and the battery supplies power to the device body.

[0017] In the present application, the liquid-absorbing particles include a liquid-absorbing core layer and a shell, and the shell is coated on the periphery of the liquid-absorbing core layer. When the negative electrode plate is applied to a battery and the battery is in normal working condition, the shell is used to isolate the liquid-absorbing core layer and the electrolyte to prevent the liquid-absorbing core layer from contacting with the electrolyte and absorbing too much electrolyte to avoid the loss of the liquid-absorbing core layer. When the battery is in an overcharged state, the temperature of the battery is high, the shell melts to expose the liquid-absorbing core layer, and the liquid-absorbing core layer absorbs the electrolyte in the battery to consume the content of the electrolyte in the battery, thereby increasing the internal resistance of the battery, aggravating the polarization phenomenon of the battery, allowing the battery to quickly reach the charging cut-off voltage, shortening the time the battery is in an overcharged state, and reducing the remaining power of the battery after the battery reaches the cut-off voltage, thereby reducing the heat generation of the battery in an overcharged state and improving the safety performance of the battery. In addition, in the overcharge state, the liquid absorbing core layer consumes a large amount of electrolyte, which is beneficial to reduce the side reaction between the electrolyte and the active particles of the negative electrode plate, thereby further reducing the heat generation inside the battery and reducing the probability of thermal runaway of the battery, so that the battery has higher safety performance in the overcharge state. It can be seen from the negative electrode plate of the present application that the liquid absorbing performance of the liquid absorbing particles has a "thermal trigger effect", that is, when the temperature of the battery reaches a certain level, the shell melts and the liquid absorbing core layer is exposed, and the liquid absorbing core layer can exert its liquid absorbing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 A schematic diagram of the structure of a battery according to an embodiment of the present application;

[0020] Figure 2 This is a schematic structural diagram of a negative electrode sheet according to an embodiment of the present application;

[0021] Figure 3 This is a schematic structural diagram of a liquid absorbing particle according to an embodiment of the present application;

[0022] Figure 4 The voltage and temperature variation curves of the implementation battery 1 and the comparison battery 2 over time;

[0023] Figure 5 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application;

[0024] Figure 6 This is a circuit block diagram of an electrical device according to an embodiment of the present application.

[0025] Description of reference numerals:

[0026] 100 - negative electrode plate, 110 - negative electrode current collector layer, 120 - negative electrode material layer, 121 - liquid absorbing particles, 1211 - liquid absorbing core layer, 1212 - shell, 200 - battery, 210 - diaphragm, 220 - positive electrode plate, 230 - electrolyte, 300 - electrical equipment, 310 - equipment body. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0029] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0030] With the continuous development of battery technology, it is particularly necessary to conduct overcharge tests on batteries to ensure the safety performance of batteries. The battery generates severe heat during the overcharge process, which will induce side reactions inside the battery. If the battery's overcharge performance is poor, thermal runaway may occur.

[0031] In order to ensure the overcharge performance of the battery, it is common to design the electrochemical balance in the battery or improve the safety protection of the battery module. However, the safety performance of the battery and the electrochemical performance of the battery are mutually constrained, that is, the better the electrochemical performance of the battery, the lower its safety performance; in addition, the structural design of the battery module to improve the protection performance has little effect on improving the overcharge performance of the battery, and the R&D cost is too high. Therefore, how to improve the safety performance of the battery in the overcharge state without sacrificing the electrochemical performance of the battery and controlling the R&D cost is an urgent problem to be solved.

[0032] See also Figures 1 to 3 The present application provides a battery 200, which includes: a negative electrode sheet 100, a separator 210, a positive electrode sheet 220 and an electrolyte 230 provided in the present application, wherein the separator 210 is arranged on one side of the negative electrode sheet 100; the positive electrode sheet 220 is arranged on the side of the separator 210 away from the negative electrode sheet 100; the electrolyte 230 is used to infiltrate at least part of the negative electrode sheet 100, the separator 210 and the positive electrode sheet 220.

[0033] It can be understood that the negative electrode plate 100, the separator 210 and the positive electrode plate 220 are stacked in sequence.

[0034] In this embodiment, the electrolyte 230 is used to infiltrate at least a portion of the negative electrode plate 100, the diaphragm 210 and the positive electrode plate 220. When the battery 200 is in an overcharged state, the temperature inside the battery 200 increases, and the outer shell 1212 of the liquid-absorbing particles 121 of the negative electrode plate 100 melts due to the high temperature to expose the liquid-absorbing core layer 1211 and adsorb the electrolyte 230, so as to quickly consume a large amount of electrolyte 230 in the battery 200, aggravate the polarization phenomenon of the battery 200, so that the voltage of the battery 200 quickly reaches the cut-off voltage, and reduce the heat generation of the battery 200 in the overcharged state, so as to avoid thermal runaway of the battery 200. The battery 200 has good safety performance and cycle performance in the overcharged state.

[0035] The present application provides a negative electrode plate 100, which includes: a negative electrode current collector layer 110 and a negative electrode material layer 120, wherein the negative electrode current collector layer 110 and the negative electrode material layer 120 are stacked, and the negative electrode material layer 120 includes liquid absorbing particles 121, and the liquid absorbing particles 121 include a liquid absorbing core layer 1211 and a shell 1212, wherein the shell 1212 is coated on the outer periphery of the liquid absorbing core layer 1211, and the shell 1212 is a polymer shell layer, and the melting temperature T of the shell 1212 is in the range of 100°C≤T≤150°C.

[0036] Specifically, the melting temperature T of the shell 1212 may be, but is not limited to, 100°C, 105°C, 110°C, 113°C, 118°C, 120°C, 124°C, 128°C, 130°C, 135°C, 140°C, 142°C, 148°C and 150°C, etc.

[0037] It can be understood that in the negative electrode material layer 120 , there are a plurality of liquid absorbing particles 121 , and the plurality of liquid absorbing particles 121 are dispersed in the negative electrode material layer 120 .

[0038] It can be understood that the negative electrode material layer 120 also includes active particles, the number of which is multiple, and the active particles are mixed and dispersed in the negative electrode material layer 120 with the liquid absorbing particles 121. The active particles can be but are not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon and activated carbon.

[0039] In this embodiment, the liquid absorbing particles 121 include a liquid absorbing core layer 1211 and an outer shell 1212, and the outer shell 1212 is coated on the periphery of the liquid absorbing core layer 1211. When the negative electrode plate 100 is applied to the battery 200 and the battery 200 is in normal working condition, the outer shell 1212 is used to isolate the liquid absorbing core layer 1211 and the electrolyte 230 to avoid the liquid absorbing core layer 1211 from contacting with the electrolyte 230 and absorbing too much electrolyte 230, so as to avoid the loss of the liquid absorbing core layer 1211. When the battery 200 is in an overcharged state, the temperature of the battery 200 is high, and the outer shell 1212 melts to expose the liquid absorbing core layer 1211. The liquid absorbing core layer 1211 absorbs the electrolyte 230 in the battery 200 to consume the content of the electrolyte 230 in the battery 200, thereby increasing the internal resistance of the battery 200 to intensify the polarization phenomenon of the battery 200, so that the battery 200 quickly reaches the charging cut-off voltage, shortens the time when the battery 200 is in the overcharged state, and reduces the remaining power of the battery 200 after the battery 200 reaches the cut-off voltage, thereby reducing the heat generation of the battery 200 in the overcharged state and improving the safety performance of the battery 200. In addition, in the overcharge state, the liquid absorbing core layer 1211 consumes a large amount of electrolyte 230, which is conducive to reducing the side reaction between the electrolyte 230 and the active particles of the negative electrode plate 100, thereby further reducing the heat generation inside the battery 200 and reducing the probability of thermal runaway of the battery 200, so that the battery 200 has higher safety performance in the overcharge state. It can be seen from the negative electrode plate 100 of this embodiment that the liquid absorbing performance of the liquid absorbing particles 121 has a "thermal trigger effect", that is, when the temperature of the battery 200 reaches a certain level, the shell 1212 melts and the liquid absorbing core layer 1211 is exposed, and the liquid absorbing core layer 1211 can exert its liquid absorbing performance.

[0040] When the melting temperature T of the shell 1212 satisfies the range of 100°C≤T≤150°C, the melting temperature of the shell 1212 is within a reasonable range, so that the shell 1212 of the liquid absorbing particle 121 can melt when the battery 200 is in an overcharged state and the temperature is high, so as to expose the liquid absorbing core layer 1211 and absorb a large amount of electrolyte 230, so that the battery 200 quickly reaches the cut-off voltage, and improves the overcharge performance of the battery 200. When the melting temperature of the shell 1212 is too high, when the battery 200 is in an overcharged state and the temperature of the battery 200 is high, the shell 1212 is difficult to melt, the shell 1212 is still covered on the periphery of the liquid absorbing core layer 1211, and the liquid absorbing core layer 1211 cannot be exposed to play the liquid absorbing function, so that the battery 200 generates more heat in the overcharged state, which increases the probability of thermal runaway of the battery 200, and the overcharge performance and safety performance of the battery 200 are poor. When the melting temperature of the shell 1212 is too low, the shell 1212 may melt prematurely, that is, the shell 1212 may melt when the battery 200 is in a normal working state, so that the liquid absorbing core layer 1211 is exposed and in contact with the electrolyte 230. On the one hand, it causes the loss of the electrolyte 230, increases the internal resistance of the battery 200, and thus reduces the cycle performance of the battery 200. On the other hand, compared with the reaction between the active particles and the electrolyte 230, the reaction between the liquid absorbing core layer 1211 and the electrolyte 230 is too intense, further reducing the cycle stability of the battery 200.

[0041] It can be understood that, in the terminology of the present application, when the battery 200 is in a working state, that is, the battery 200 performs a charge and discharge cycle normally.

[0042] It can be understood that, in the terminology of the present application, when the battery 200 is in an overcharged state, that is, during the charging process of the battery 200, the charging voltage or the charging amount exceeds the rated charging limit designed for the battery 200.

[0043] It can be understood that in the terminology of this application, "polarization phenomenon" refers to the phenomenon that the potential at the interface between the electrode (negative electrode sheet 100 or positive electrode sheet 220) and the electrolyte 230 deviates from the equilibrium value. When current passes through the electrode, the electrode potential deviates from its equilibrium potential.

[0044] It can be understood that, in the terminology of the present application, "charging cut-off voltage" refers to the highest charging voltage reached by the battery 200 during the charging process. When the battery 200 is charged to reach the charging cut-off voltage, the charging process will stop.

[0045] It can be understood that, in the terminology of the present application, "overcharge performance" refers to the performance of the battery 200 in an overcharged state, such as safety performance and cycle performance.

[0046] Preferably, the melting temperature T of the shell 1212 is in the range of 110°C ≤ T ≤ 135°C.

[0047] Optionally, when the negative electrode plate 100 is applied to the battery 200 and the battery 200 is in an overcharged state, the highest temperature in the battery 200 is T', and the relationship is satisfied: 10°C ≤ T'-T ≤ 30°C.

[0048] Specifically, the value of T'-T may be, but is not limited to, 10°C, 11°C, 12°C, 15°C, 16°C, 18°C, 20°C, 22°C, 23°C, 24°C, 26°C, 28°C, and 30°C.

[0049] In this embodiment, the melting temperature of the shell 1212 is lower than the highest temperature of the battery 200 in the overcharge state, so that when the battery 200 is in the overcharge state, the shell 1212 melts and exposes the liquid absorbing core layer 1211, so that the liquid absorbing core layer 1211 can play a liquid absorbing function, aggravate the polarization of the battery 200, make the battery 200 quickly reach the charging cut-off voltage, reduce the heat generation of the battery 200 in the overcharge state, and improve the safety performance of the battery 200. If the value of T'-T is too large, the shell 1212 may melt too early, and the overcharge state may be misidentified, resulting in the loss of the liquid absorbing core layer 1211, thereby shortening the service life of the negative electrode plate 100. If the value of T'-T is too small, the shell 1212 may melt too late, so that the liquid absorbing core layer 1211 cannot fully play the function of absorbing liquid, thereby reducing the safety performance of the battery 200 in the overcharge state.

[0050] Optionally, in some embodiments, when the negative electrode plate 100 is applied to the battery 200 and the battery 200 is in an overcharge state, the maximum temperature in the battery 200 is 130°C.

[0051] In some embodiments, the conductivity σ of the housing 1212 is in the range of: 10 -12 S / m≤σ≤10 -9 S / m.

[0052] Specifically, the value of the conductivity σ of the housing 1212 may be, but is not limited to, 10 -12 S / m, 2×10 -12 S / m, 4×10 -12 S / m, 8×10 -12 S / m, 9×10 -12 S / m, 10 -11 S / m, 2×10 -11 S / m, 4×10 -11 S / m, 8×10 -11S / m, 9×10 -11 S / m, 10 -10 S / m, 2×10 -10 S / m, 4×10 -10 S / m, 8×10 -10 S / m, 9×10 -10 S / m, 10 -9 S / m.

[0053] In this embodiment, the conductivity σ of the housing 1212 satisfies the range of 10 -12 S / m≤σ≤10 -9 S / m, in other words, the conductivity of the shell 1212 is extremely low or the shell 1212 has electronic insulation properties. When the negative electrode plate 100 is applied to the battery 200, when the battery 200 is in normal working condition, the shell 1212 is coated on the periphery of the liquid absorbing core layer 1211, and the shell 1212 isolates the electron transfer between the electrolyte 230 and the liquid absorbing core layer 1211, so that the liquid absorbing core layer 1211 cannot react electrochemically with the electrolyte 230. On the one hand, it can avoid that the liquid absorbing core layer 1211 reacts too violently with the electrolyte 230 and reduces the cycle stability; on the other hand, it can avoid that the liquid absorbing core layer 1211 is lost too much, so that the liquid absorbing function of the liquid absorbing particles 121 is reduced when the battery 200 is in an overcharged state. When the conductivity of the shell 1212 is too large, when the battery 200 is in working state, electrons can still be transmitted between the electrolyte 230 and the liquid absorbing core layer 1211, so that the liquid absorbing core layer 1211 and the electrolyte 230 undergo electrochemical reaction, resulting in loss of the liquid absorbing core layer 1211. When the battery 200 is in an overcharged state, the shell 1212 melts and exposes the liquid absorbing core layer 1211, and the content of the liquid absorbing core layer 1211 in the liquid absorbing particles 121 is reduced, so that the amount of electrolyte 230 absorbed by the liquid absorbing core layer 1211 is reduced, so that the content of electrolyte 230 in the battery 200 is still too much. When the battery 200 reaches the charging cut-off voltage, the SOC of the battery 200 is high, and the heat generation of the battery 200 in the overcharged state is high, which increases the risk of thermal runaway of the battery 200.

[0054] It is understandable that in the terminology of the present application, "SOC" stands for "State of Charge", which is translated into Chinese as "state of charge" and is a parameter used to describe the remaining power of the battery 200. It represents the ratio of the power currently stored in the battery 200 to the power that can be stored when the battery 200 is fully charged, usually expressed as a percentage. The value range of SOC is usually between 0% and 100%, where when SOC is 0%, it means that the battery 200 is fully discharged, and when SOC is 100%, it means that the battery 200 is fully charged.

[0055] Optionally, the conductivity of the liquid absorbing core layer 1211 is σ', which satisfies the relationship: 10 3 ≤σ' / σ≤10 9 .

[0056] It can be understood that the conductivity of the liquid absorbing core layer 1211 is much greater than the conductivity of the outer shell 1212 .

[0057] Specifically, the value of σ' / σ can be, but is not limited to, 10 3 , 2×10 3 , 8×10 3 , 10 4 , 2×10 4 , 8×10 4 , 10 5 , 2×10 5 , 8×10 5 , 10 6 , 2×10 6 , 8×10 6 , 10 7 , 2×10 7 , 8×10 7 , 10 8 , 2×10 8 , 8×10 8 , 10 9 .

[0058] In this embodiment, the ratio of the conductivity of the liquid absorbing core layer 1211 to the conductivity of the shell 1212 is within a reasonable range, the conductivity of the shell 1212 is much smaller than the conductivity of the liquid absorbing core layer 1211, the conductivity of the shell 1212 is extremely low or the shell 1212 has electronic insulation properties. When the negative electrode plate 100 is applied to the battery 200, when the battery 200 is in normal working condition, the shell 1212 is coated on the periphery of the liquid absorbing core layer 1211, and the shell 1212 isolates the electron transfer between the electrolyte 230 and the liquid absorbing core layer 1211, so that the liquid absorbing core layer 1211 cannot undergo electrochemical reaction with the electrolyte 230. When the battery 200 is in an overcharged state, the outer shell 1212 melts and exposes the liquid absorbing core layer 1211 . The liquid absorbing core layer 1211 has a higher electrical conductivity so that the liquid absorbing core layer 1211 can absorb more electrolyte 230 .

[0059] Optionally, the conductivity σ' of the liquid absorbing core layer 1211 is in the range of: 10 -6 S / m≤σ'≤10 -4 The liquid absorption core layer 1211 has good electron transport performance, so that the liquid absorption core layer 1211 has good performance of absorbing the electrolyte 230.

[0060] Specifically, the value of the conductivity σ' of the liquid absorbing core layer 1211 may be, but is not limited to, 10 -6 S / m, 2×10 -6 S / m, 4×10 -6 S / m, 8×10 -6 S / m, 9×10 -6 S / m, 10 -5 S / m, 2×10 -5 S / m, 4×10 -5 S / m, 8×10 -5 S / m, 9×10 -5 S / m, 10 -4 S / m.

[0061] In some embodiments, the range of the liquid absorption amount Q of the liquid absorbing particles 121 per unit mass is: 3 mL / g≤Q≤7 mL / g.

[0062] Specifically, the value of the liquid absorption amount Q of the liquid absorbing particles 121 per unit mass can be but is not limited to 3 mL / g, 3.5 mL / g, 4 mL / g, 4.5 mL / g, 5 mL / g, 5.5 mL / g, 6 mL / g, 6.5 mL / g and 7 mL / g.

[0063] It can be understood that the liquid absorption amount Q of the liquid absorbing particles 121 per unit mass is the volume of the electrolyte 230 that can be absorbed by the liquid absorbing particles 121 per unit mass.

[0064] In this embodiment, when the liquid absorption amount Q of the liquid absorbing particles 121 per unit mass satisfies the range of 3mL / g≤Q≤7mL / g, the liquid absorption amount of the liquid absorbing particles 121 is within a reasonable range, in other words, the liquid absorption performance of the liquid absorbing particles 121 is within a reasonable range. When the negative electrode plate 100 is applied to the battery 200 and the battery 200 is in an overcharged state, the outer shell 1212 of the liquid absorbing particles 121 melts, and the liquid absorbing core layer 1211 can quickly absorb a large amount of electrolyte 230 to reduce the content of free electrolyte 230 in the battery 200, thereby increasing the internal resistance of the battery 200, aggravating the polarization phenomenon of the battery 200, allowing the battery 200 to quickly reach the charging cut-off voltage, shortening the time the battery 200 is in the overcharge state, and reducing the remaining power of the battery 200 after the battery 200 reaches the cut-off voltage, thereby reducing the heat generation of the battery 200 in the overcharge state and improving the safety performance of the battery 200. In addition, in the overcharge state, the liquid absorbing core layer 1211 consumes a large amount of electrolyte 230, which is beneficial to reduce the side reaction between the electrolyte 230 and the active particles of the negative electrode plate 100, thereby further reducing the heat generation inside the battery 200 and reducing the probability of thermal runaway of the battery 200, so that the battery 200 has higher safety performance in the overcharge state. When the liquid absorption amount of the liquid absorbing particles 121 is too large, it means that the specific surface area of ​​the liquid absorbing core layer 1211 is too large, which increases the processing difficulty of the liquid absorbing particles 121. When the liquid absorption amount of the liquid absorbing particles 121 is too small, when the battery 200 is in the overcharge state and the shell 1212 melts, although the liquid absorbing particles 121 can absorb part of the electrolyte 230, the liquid absorption effect of the liquid absorbing particles 121 is not obvious, and the battery 200 may still generate more heat in the overcharge state, and the overcharge performance of the battery 200 is poor.

[0065] In some embodiments, the liquid absorption amount Q' of the negative electrode plate 100 per unit area is in the range of: 0.8 mL / cm 2 ≤Q'≤2mL / cm 2 .

[0066] It can be understood that the amount of liquid absorbed Q per unit mass of the liquid-absorbing particles 121 is positively correlated with the amount of liquid absorbed Q' per unit area of ​​the negative electrode plate 100. When the amount of liquid absorbed Q per unit mass of the liquid-absorbing particles 121 is larger, the amount of liquid absorbed Q' per unit area of ​​the negative electrode plate 100 is larger; when the amount of liquid absorbed Q per unit mass of the liquid-absorbing particles 121 is smaller, the amount of liquid absorbed Q' per unit area of ​​the negative electrode plate 100 is smaller.

[0067] It can be understood that when the negative electrode sheet 100 is treated at 150° C. for 30 minutes, the liquid absorption amount Q' of the negative electrode sheet 100 per unit mass is in the range of: 0.8 mL / cm 2 ≤Q'≤2mL / cm 2 In the embodiment of the present application, the treatment for 30 minutes is to place the negative electrode plate 100 in the electrolyte 230 for 30 minutes to test the liquid absorption of the negative electrode plate 100 .

[0068] In this embodiment, when the liquid absorption amount Q' per unit area of ​​the negative electrode plate 100 satisfies the range of 0.8 mL / cm 2 ≤Q'≤2mL / cm 2 When the negative electrode plate 100 is applied to the battery 200 and the battery 200 is in an overcharged state, the outer shell 1212 of the liquid absorbing particle 121 melts, and the liquid absorbing core layer 1211 can quickly absorb a large amount of electrolyte 230 to reduce the content of free electrolyte 230 in the battery 200, thereby increasing the internal resistance of the battery 200, so as to aggravate the polarization phenomenon of the battery 200, so that the battery 200 quickly reaches the charging cut-off voltage, shortens the time when the battery 200 is in the overcharged state, and reduces the remaining power of the battery 200 after the battery 200 reaches the cut-off voltage, thereby reducing the heat generation of the battery 200 in the overcharged state and improving the safety performance of the battery 200.

[0069] In some embodiments, the median particle size d1 of the liquid absorbing core layer 1211 is in the range of 10 nm ≤ d1 ≤ 500 nm.

[0070] Specifically, the median particle size d1 of the liquid absorbing core layer 1211 can be, but is not limited to, 10nm, 20nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, 220nm, 280nm, 300nm, 350nm, 380nm, 400nm, 420nm, 450nm, 480nm and 500nm, etc.

[0071] It can be understood that the particle size of the liquid absorbing core layer 1211 is the maximum radial dimension of the liquid absorbing core layer 1211. Further, the particle size of the liquid absorbing core layer 1211 is the diameter of the liquid absorbing core layer 1211.

[0072] It can be understood that the median particle size of the liquid absorbing core layer 1211 is the particle size corresponding to the mass of particles smaller than the median particle size accounting for 50% of the total mass of the particles on the particle size distribution curve of the liquid absorbing core layer 1211 .

[0073] In this embodiment, when the median particle size d1 of the liquid absorbing core layer 1211 satisfies the range of 10nm≤d1≤500nm, the median particle size of the liquid absorbing core layer 1211 is within a reasonable range, and the median particle size of the liquid absorbing core layer 1211 is at the nanometer level, so that the liquid absorbing core layer 1211 has a larger specific surface area, and when the outer shell 1212 melts and the liquid absorbing core layer 1211 is exposed, the liquid absorbing core layer 1211 can be in full contact with the electrolyte 230, so that the liquid absorbing particles 121 have a larger liquid absorption amount. The liquid-absorbing particles 121 can quickly reduce the amount of free electrolyte 230 in the battery 200 to intensify the polarization phenomenon of the battery 200, so that the battery 200 quickly reaches the cut-off voltage to reduce the heat generation of the battery 200 in the overcharge state, thereby reducing the risk of thermal runaway of the battery 200 due to excessive heat generation in the overcharge state, and improving the safety performance and cycle performance of the battery 200 in the overcharge state. When the median particle size of the liquid absorbing core layer 1211 is too large, the specific surface area of ​​the liquid absorbing core layer 1211 is reduced accordingly. Then, when the outer shell 1212 melts and the liquid absorbing core layer 1211 is exposed, the contact area between the liquid absorbing core layer 1211 and the electrolyte 230 becomes smaller, which reduces the efficiency of the liquid absorbing core layer 1211 in adsorbing the electrolyte 230, and ultimately makes the liquid absorption amount of the liquid absorbing particles 121 too small. When the battery 200 is in an overcharged state and the outer shell 1212 melts, although the liquid absorbing particles 121 can absorb part of the electrolyte 230, the liquid absorption effect of the liquid absorbing particles 121 is not obvious, and the battery 200 may still generate more heat in the overcharged state, and the overcharge performance of the battery 200 is poor. When the median particle size of the liquid absorbing core layer 1211 is too small, during the preparation process of the liquid absorbing particles 121, the shell 1212 is difficult to cover the periphery of the liquid absorbing core layer 1211, which increases the difficulty of preparing the liquid absorbing particles 121 and increases the preparation cost of the liquid absorbing particles 121.

[0074] Preferably, the range of the median particle size d1 of the liquid absorbing core layer 1211 is: 10 nm≤d1≤110 nm.

[0075] In some embodiments, the specific surface area S of the liquid absorbing core layer 1211 is in the range of: 1.1 m 2 / g≤S≤1.7m 2 / g.

[0076] Specifically, the specific surface area S of the liquid absorbing core layer 1211 may be, but is not limited to, 1.1 m 2 / g, 1.15m 2 / g, 1.2m 2 / g, 1.25m 2 / g, 1.3m 2 / g, 1.35m 2 / g, 1.4m 2 / g, 1.46m 2 / g, 1.5m 2 / g, 1.55m 2 / g, 1.6m 2 / g, 1.62m 2 / g, 1.65m 2 / g and 1.7m 2 / g, etc.

[0077] In this embodiment, when the specific surface area S of the liquid absorbing core layer 1211 satisfies the range of 1.1 m 2 / g≤S≤1.7m 2 / g, the specific surface area of ​​the liquid absorbing core layer 1211 is within a reasonable range. When the shell 1212 melts and the liquid absorbing core layer 1211 contacts the electrolyte 230, the liquid absorbing core layer 1211 can fully contact the electrolyte 230 and absorb the electrolyte 230, so that the liquid absorption amount of the liquid absorbing particles 121 is within a reasonable range. When the battery 200 is in an overcharged state, the shell 1212 of the liquid absorbing particles 121 melts, and the liquid absorbing core layer 1211 can quickly absorb a large amount of electrolyte 230 to reduce the content of free electrolyte 230 in the battery 200, thereby increasing the internal resistance of the battery 200, aggravating the polarization phenomenon of the battery 200, making the battery 200 quickly reach the charging cut-off voltage, shortening the time when the battery 200 is in the overcharged state, and reducing the remaining power of the battery 200 after the battery 200 reaches the cut-off voltage, thereby reducing the heat generation of the battery 200 in the overcharged state and improving the safety performance of the battery 200. In addition, in the overcharge state, the liquid absorbing core layer 1211 consumes a large amount of electrolyte 230, which is conducive to reducing the side reaction between the electrolyte 230 and the active particles of the negative electrode plate 100, thereby further reducing the heat generation inside the battery 200 and reducing the probability of thermal runaway of the battery 200, so that the battery 200 has higher safety performance in the overcharge state. When the specific surface area of ​​the liquid absorbing core layer 1211 is too large, the existing production process cannot meet the production of core layer materials with a larger specific surface area, which increases the difficulty of preparing the liquid absorbing core layer 1211, and when the liquid absorbing core layer 1211 is coated with a shell layer, it is easy to cause the liquid absorbing core layer 1211 to agglomerate, making the uniformity of the liquid absorbing core layer 1211 poor, and reducing the performance of the liquid absorbing particles 121. When the specific surface area of ​​the liquid absorbing core layer 1211 is too small, when the outer shell 1212 melts and the liquid absorbing core layer 1211 is exposed, the contact area between the liquid absorbing core layer 1211 and the electrolyte 230 becomes smaller, reducing the efficiency of the liquid absorbing core layer 1211 in adsorbing the electrolyte 230, and ultimately making the liquid absorption amount of the liquid absorbing particles 121 too small. When the battery 200 is in an overcharged state and the outer shell 1212 melts, although the liquid absorbing particles 121 can absorb part of the electrolyte 230, the liquid absorption effect of the liquid absorbing particles 121 is not obvious, and the battery 200 may still generate more heat in the overcharged state, and the overcharge performance of the battery 200 is poor.

[0078] Preferably, the specific surface area S of the liquid absorbing core layer 1211 is in the range of: 1.3 m 2 / g≤S≤1.4m 2 / g.

[0079] In some embodiments, the thickness of the shell 1212 is h, and the median particle size of the liquid absorbing particles 121 is d2, then the relationship is satisfied: 0.3≤h / d2≤0.5.

[0080] Specifically, the value of h / d2 can be, but is not limited to, 0.3, 0.32, 0.35, 0.38, 0.39, 0.4, 0.42, 0.44, 0.46, 0.48 and 0.5, etc.

[0081] It can be understood that the particle size of the liquid absorbing particle 121 is the maximum radial dimension of the liquid absorbing particle 121. Further, the particle size of the liquid absorbing particle 121 is the diameter of the liquid absorbing particle 121.

[0082] It can be understood that the median particle size of the liquid absorbing particles 121 is the particle size corresponding to the mass of particles smaller than the median particle size accounting for 50% of the total mass of the particles on the particle size distribution curve of the liquid absorbing particles 121 .

[0083] In this embodiment, when the liquid absorbing particles 121 satisfy the relationship 0.3≤h / d2≤0.5, the thickness h of the shell 1212 and the median particle size d2 of the liquid absorbing particles 121 are both within a reasonable range. In other words, the thickness of the shell 1212 and the radius of the liquid absorbing core layer 1211 are both within a reasonable range. When the battery 200 is in a working state, the shell 1212 can protect the liquid absorbing core layer 1211 to isolate the electrolyte 230 and the liquid absorbing core layer 1211, thereby avoiding the loss of the liquid absorbing core layer 1211. When the battery 200 is in an overcharged state, the shell 1212 is easy to melt at a high temperature, so that the liquid absorbing core layer 1211 is exposed and performs the liquid absorbing function, and finally enables the battery 200 to have better cycle performance and safety performance in an overcharged state. When the value of h / d2 is too large, the thickness of the shell 1212 is too large or the median particle size of the liquid absorbing particle 121 is too small. In other words, the thickness of the shell 1212 is too large or the radius of the liquid absorbing core layer 1211 is too small. On the one hand, in the liquid absorbing particle 121, the mass content of the liquid absorbing core layer 1211 is too small, which reduces the amount of liquid absorbed by the liquid absorbing particle 121. On the other hand, it is more difficult to cover the shell 1212 on the liquid absorbing core layer 1211, and the preparation cost of the liquid absorbing particle 121 is increased. In addition, when the battery 200 is in an overcharged state, even if the temperature inside the battery 200 reaches the melting temperature of the shell 1212, the coating layer is still difficult to melt or partially melts, so that the liquid absorbing core layer 1211 cannot be quickly exposed, so that the contact area between the liquid absorbing core layer 1211 and the electrolyte 230 is small, which in turn reduces the amount of liquid absorbed by the liquid absorbing particles 121 to the electrolyte 230, so that the battery 200 may still generate more heat in the overcharged state, and the overcharge performance of the battery 200 is poor. When the value of h / d2 is too small, the thickness of the shell 1212 is too small or the median particle size of the liquid absorbing particles 121 is too large. In other words, the thickness of the shell 1212 is too small or the radius of the liquid absorbing particles 121 is too large. When the battery 200 is in a normal working state, the coating layer is too thin and easy to break, so that the electrolyte 230 in the battery 200 is easy to pass through the coating layer and contact with the liquid absorbing core layer 1211. On the one hand, the liquid absorbing core layer 1211 is lost, so that the liquid absorbing performance of the liquid absorbing core layer 1211 decreases; on the other hand, the reaction between the liquid absorbing core layer 1211 and the electrolyte 230 is too violent, and more side reaction products may be produced during the reaction between the liquid absorbing core layer 1211 and the electrolyte 230, thereby reducing the cycle stability of the battery 200.

[0084] In some embodiments, the thickness h of the shell 1212 is in the range of 20 nm ≤ h ≤ 300 nm.

[0085] Specifically, the thickness h of the shell 1212 can be, but is not limited to, 20 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 160 nm, 180 nm, 200 nm, 220 nm, 250 nm, 280 nm, and 300 nm.

[0086] In this embodiment, when the thickness h of the shell 1212 satisfies the range of 20nm≤h≤300nm, the thickness of the shell 1212 is within a reasonable range. When the battery 200 is in a normal working state, the shell 1212 can be used as a protective layer to isolate the electrolyte 230 and the liquid absorbing core layer 1211, so as to prevent the electrolyte 230 from passing through the shell 1212 and entering the liquid absorbing core layer 1211, thereby avoiding the loss of the liquid absorbing core layer 1211. When the battery 200 is in an overcharged state, the shell 1212 is easy to melt to quickly and completely expose the liquid absorbing core layer 1211, so that the liquid absorbing core layer 1211 can give full play to the liquid absorbing function, so as to quickly consume the amount of the electrolyte 230 in the battery 200, so that the battery 200 has better safety performance and cycle performance in the overcharged state. When the thickness of the shell 1212 is too large, when the battery 200 is in an overcharged state, even if the temperature inside the battery 200 reaches the melting temperature of the shell 1212, the coating layer is still difficult to melt or partially melts, so that the liquid absorbing core layer 1211 cannot be quickly exposed, so that the contact area between the liquid absorbing core layer 1211 and the electrolyte 230 is small, and then the amount of liquid absorbed by the liquid absorbing particles 121 to the electrolyte 230 is reduced, so that the battery 200 may still generate more heat in the overcharged state, and the overcharge performance of the battery 200 is poor. When the thickness of the shell 1212 is too small, when the battery 200 is in a normal working state, the coating layer is too thin and easy to break, so that the electrolyte 230 in the battery 200 is easy to pass through the coating layer and contact with the liquid absorbing core layer 1211. On the one hand, the liquid absorbing core layer 1211 is lost, so that the liquid absorbing performance of the liquid absorbing core layer 1211 decreases; on the other hand, the reaction between the liquid absorbing core layer 1211 and the electrolyte 230 is too violent, and more side reaction products may be produced during the reaction between the liquid absorbing core layer 1211 and the electrolyte 230, thereby reducing the cycle stability of the battery 200.

[0087] Preferably, the thickness h of the shell 1212 is in the range of 20 nm ≤ h ≤ 200 nm.

[0088] In some embodiments, the median particle size d2 of the liquid absorbing particles 121 is in the range of 20 nm≤d2≤1000 nm.

[0089] Specifically, the median particle size d2 of the liquid-absorbing particles 121 can be, but is not limited to, 20 nm, 45 nm, 50 nm, 65 nm, 80 nm, 90 nm, 100 nm, 120 nm, 135 nm, 150 nm, 180 nm, 200 nm, 250 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 750 nm, 800 nm, 900 nm and 1000 nm, etc.

[0090] In this embodiment, when the median particle size d of the liquid-absorbing particles 121 satisfies the range of 20nm≤d2≤1000nm, the median particle size of the liquid-absorbing particles 121 is within a reasonable range, and the liquid-absorbing particles 121 are neither too large nor too small, so that during the preparation process of the negative electrode plate 100, the liquid-absorbing particles 121 can be uniformly dispersed in the negative electrode material layer 120 with the active particles, so that the negative electrode plate 100 has good structural stability and can avoid the agglomeration of the liquid-absorbing particles 121. When the battery 200 is in a working state, the liquid-absorbing particles 121 can avoid increasing the internal resistance of the battery 200, so that the battery 200 has good cycle stability. When the battery 200 is in an overcharged state, the liquid-absorbing particles 121 can fully exert the function and effect of absorbing the electrolyte 230, and reduce the heat generation of the battery 200 in the overcharged state, so that the battery 200 has good safety performance and cycle performance in the overcharged state. When the median particle size d2 of the liquid-absorbing particles 121 is too large, during the preparation of the negative electrode sheet 100, when the negative electrode material layer 120 is disposed on one side of the negative electrode collector layer 110, the liquid-absorbing particles 121 are likely to cause the negative electrode sheet 100 to rupture and pulverize, thereby increasing the difficulty in the preparation of the negative electrode sheet 100, and reducing the structural stability of the negative electrode sheet 100, and ultimately shortening the cycle life of the negative electrode sheet 100; in addition, the liquid-absorbing particles 121 and the active particles are distributed in the negative electrode material layer 120, and the liquid-absorbing particles 121 block the channels for the transmission of active ions between the active particles, affecting the electron pathway inside the negative electrode sheet 100, and increasing the internal resistance of the negative electrode sheet 100. When the median particle size d2 of the liquid-absorbing particles 121 is too small, the liquid-absorbing particles 121 are prone to agglomeration during the preparation of the negative electrode plate 100, and the liquid-absorbing particles 121 cannot be evenly dispersed in the negative electrode material layer 120. The agglomeration of multiple liquid-absorbing particles 121 also affects the electron path inside the negative electrode plate 100. Furthermore, when the battery 200 is in an overcharged state, it is more difficult to melt the outer shells 1212 of the multiple liquid-absorbing particles 121 that form agglomerates, making it difficult for the liquid-absorbing particles 121 to play a liquid-absorbing role, and ultimately affecting the safety performance and cycle performance of the battery 200.

[0091] Preferably, the median particle size d2 of the liquid absorbing particles 121 is in the range of 20 nm ≤ d2 ≤ 300 nm.

[0092] In some embodiments, in the negative electrode material layer 120 , the mass fraction a of the liquid absorbing particles 121 is in the range of 0.1%≤a≤0.5%.

[0093] It can be understood that in the negative electrode material layer 120 , the mass fraction a of the liquid absorbing particles 121 is the ratio of the sum of the masses of all the liquid absorbing particles 121 to the mass of the negative electrode material layer 120 .

[0094] Specifically, in the negative electrode material layer 120, the mass fraction a of the liquid absorbing particles 121 can be but is not limited to 0.1%, 0.12%, 0.15%, 0.2%, 0.22%, 0.26%, 0.3%, 0.35%, 0.4%, 0.42%, 0.45% and 0.5%, etc.

[0095] In this embodiment, when the mass fraction a of the liquid-absorbing particles 121 satisfies the range of 0.1%≤a≤0.5%, the mass fraction of the liquid-absorbing particles 121 is within a reasonable range. On the one hand, by adding a small amount of the liquid-absorbing particles 121 to the negative electrode material layer 120, the safety performance and cycle performance of the battery 200 in an overcharge state can be effectively improved. On the other hand, the mass content of the liquid-absorbing particles 121 is small, which can avoid reducing the energy density of the negative electrode plate 100 and avoid damaging the structure of the negative electrode plate 100, so that the negative electrode plate 100 has good structural stability and a long service life. When the mass fraction a of the liquid-absorbing particles 121 is too large, then correspondingly, in the negative electrode material layer 120, the mass fraction of the active particles is too small, and the liquid-absorbing particles 121 occupy too much mass and volume of the negative electrode material layer 120, thereby reducing the mass and volume of the active particles occupying the negative electrode material layer 120, reducing the energy density of the negative electrode plate 100, and thus reducing the charge and discharge efficiency of the battery 200. When the mass fraction a of the liquid-absorbing particles 121 is too small, when the battery 200 is in an overcharged state, even if the outer shells 1212 of all the liquid-absorbing particles 121 are melted, the total amount of electrolyte 230 that can be adsorbed by the liquid-absorbing core layer 1211 is still small, and the effect of the liquid-absorbing particles 121 on aggravating the polarization of the battery 200 is not obvious. The heat generated by the battery 200 in the overcharged state is still large, and the overcharge performance of the battery 200 is still poor.

[0096] Preferably, the mass fraction a of the liquid absorbing particles 121 is in the range of 0.1%≤a≤0.3%.

[0097] In some embodiments, the liquid absorbing core layer 1211 includes a silicon-based material, and the silicon-based material includes at least one of silicon dioxide, silicon, silicon carbide, and sodium silicate.

[0098] In this embodiment, the liquid absorbing core layer 1211 is the silicon-based material, and the silicon-based material is selected from at least one of silicon dioxide, silicon, silicon carbide, and sodium silicate. Silicon dioxide, silicon, silicon carbide, and sodium silicate all have the ability to electrochemically insert lithium and have a large specific surface area. When the outer shell 1212 melts and the liquid absorbing core layer 1211 is exposed, the liquid absorbing core layer 1211 can quickly absorb a large amount of electrolyte 230 to consume the free electrolyte 230 in the battery 200, thereby intensifying the polarization of the battery 200, so that the voltage of the battery 200 quickly reaches the cut-off voltage, reduces the heat generated by the battery 200 during the polarization process, and improves the overcharge performance of the battery 200.

[0099] In some embodiments, the material of the shell 1212 is selected from at least one of polyethylene, polyacrylic acid, polyimide, polyester, polyvinyl chloride, polyethylene terephthalate, and polybutylene succinate.

[0100] In this embodiment, the material of the shell 1212 is selected from at least one of polyethylene, polyacrylic acid, polyimide, polyester, polyvinyl chloride, polyethylene terephthalate and polybutylene succinate. On the one hand, polyethylene, polyacrylic acid, polyimide, polyester, polyvinyl chloride, polyethylene terephthalate and polybutylene succinate all have good electronic insulation. When the battery 200 is in normal working condition, the shell 1212 can protect the liquid absorbing core layer 1211 to prevent electrons from passing through the shell 1212 and entering the liquid absorbing core layer 1211, so as to prevent the liquid absorbing core layer 1211 from participating in the electrochemical reaction of the battery 200, thereby making the battery 200 have good electrochemical performance. On the other hand, the melting temperatures of polyethylene, polyacrylic acid, polyimide, polyester, polyvinyl chloride, polyethylene terephthalate and polybutylene succinate are within a reasonable range, so that when the battery 200 is in an overcharged state, the outer shell 1212 can be melted to expose the liquid absorbing core layer 1211 and exert its liquid absorbing performance, so that the battery 200 has better performance in the overcharged state.

[0101] The technical solution of this application is further introduced in the following with multiple embodiments:

[0102] Example 1 to Example 12, Comparative Example 1 to Example 3:

[0103] 1. Preparation of liquid-absorbing particles 121:

[0104] The silicon dioxide powder is firstly alkali washed, the pH of the alkali solution is adjusted to 8, and then filtered and dried. The acrylic acid ester monomer, emulsifier, initiator, deionized water, and silicon dioxide particles are added to the reactor in a ratio of 3:1:1:2, stirring is started, the temperature of the reactor is adjusted to 60°C, and emulsification and dispersion are carried out after continuous stirring for 70 minutes, and spherical particles are formed by spray drying, wherein the spherical particles are the liquid-absorbing particles 121, and the liquid-absorbing particles 121 include a liquid-absorbing core layer 1211 and the shell 1212, the liquid-absorbing core layer 1211 is selected from silicon dioxide, and the shell 1212 is polyethylene formed by acrylic acid ester monomers.

[0105] It can be understood that the median particle size of the liquid absorbing core layer 1211, the thickness of the shell 1212, the median particle size of the liquid absorbing particles 121 and the specific surface area of ​​the liquid absorbing core layer 1211 can be adjusted by controlling the preparation process of the liquid absorbing particles 121, which will not be repeated here.

[0106] In the liquid-absorbing particles 121 of Examples 1 to 12 and Comparative Examples 1 to 3, the median particle size d1 of the liquid-absorbing core layer 1211, the thickness h of the shell 1212, the median particle size d2 of the liquid-absorbing particles 121, and the specific surface area S of the liquid-absorbing core layer 1211 are as shown in Table 1.

[0107] 2. Preparation of negative electrode sheet 100:

[0108] The active particles of artificial graphite for the negative electrode plate 100, the thickener sodium carboxymethyl cellulose (CMC), the conductive carbon black (Super-P), the binder styrene-butadiene rubber latex (SBR), and the liquid-absorbing particles 121 are mixed according to a mass ratio, wherein the mass proportion of the thickener is 2%, the mass proportion of the conductive carbon black is 1%, the mass proportion of the binder is 1%, and the sum of the mass fraction of the active particles and the mass fraction of the liquid-absorbing particles 121 is 96%. Deionized water is added to prepare a negative electrode slurry with a solid content of 50wt%, and the mixture is stirred evenly. The negative electrode slurry is uniformly coated on one surface of a negative electrode collector layer 110 (copper foil) with a thickness of 6 μm. After drying, cold pressing, slitting and cutting, the negative electrode slurry forms a negative electrode material layer 120. The negative electrode collector layer 110 and the negative electrode material layer 120 are stacked to obtain a negative electrode sheet 100, wherein the drying temperature does not exceed 95°C, and the single-sided thickness of the negative electrode material layer 120 is 70 μm, to obtain the negative electrode sheets 100 of Examples 1 to 12 and Comparative Examples 1 to 3.

[0109] Wherein, in the negative electrode material layer 120 , the mass fraction a of the liquid absorbing particles 121 is as shown in Table 1.

[0110] 3. Preparation of positive electrode sheet 220:

[0111] The positive electrode active material lithium iron phosphate (LiFePO4), conductive carbon black (Super-P), and binder PVDF are mixed in a mass ratio of 94:3:3; then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 60wt%, and stirred evenly, and then the positive electrode slurry is evenly coated on one surface of a positive electrode collector layer (aluminum foil) with a thickness of 10μm, and then after drying, cold pressing, stripping, and cutting, the positive electrode slurry forms a positive electrode material layer, and the positive electrode collector layer and the positive electrode material layer are stacked to obtain a positive electrode sheet 220. The single-sided thickness of the positive electrode material layer is 100μm.

[0112] 4. Preparation of electrolyte 230:

[0113] In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed uniformly in a mass ratio of 1:2:1 to form a solvent; then the dried electrolyte lithium hexafluorophosphate is dissolved in the solvent and stirred until completely dissolved to obtain the electrolyte 230 of Examples 1 to 12 and Comparative Examples 1 to 3.

[0114] 5. Assembly of battery 200:

[0115] After welding the negative electrode sheet 100 and the positive electrode sheet 220 obtained above to the pole ears, the negative electrode sheet 100, the separator 210 and the positive electrode sheet 220 are wound and placed in the outer shell 1212, and the above-mentioned electrolyte 230 is injected after drying. After vacuum packaging, standing, forming, shaping, etc., the implementation battery 1 to the implementation battery 12 and the comparison battery 1 to the comparison battery 3 are finally prepared, wherein the implementation battery 1 includes the negative electrode sheet 100 and the liquid-absorbing particles 121 of Example 1, the implementation battery 2 includes the negative electrode sheet 100 and the liquid-absorbing particles 121 of Example 2, the comparison battery 1 includes the negative electrode sheet 100 and the liquid-absorbing particles 121 of the comparison example 1, the comparison battery 2 includes the negative electrode sheet 100 and the liquid-absorbing particles 121 of the comparison example 2, and the comparison battery 1 includes the negative electrode sheet 100 and the liquid-absorbing particles 121 of the comparison example 1, and the comparison battery 2 includes the negative electrode sheet 100 and the liquid-absorbing particles 121 of the comparison example 2, and so on.

[0116] Table 1: Structural parameters of the liquid absorbing particles 121 and the negative electrode sheet 100 of Examples 1 to 12 and Comparative Examples 1 to 3.

[0117]

[0118] It can be understood that in Comparative Example 1, the liquid absorbing core layer 1211 only includes the liquid absorbing core layer 1211, and the outer periphery of the liquid absorbing core layer 1211 is not covered with the shell 1212. In Comparative Example 2, the mass fraction of the liquid absorbing particles 121 is 0%, in other words, the negative electrode material layer 120 of Comparative Example 2 does not include the liquid absorbing particles 121.

[0119] Performance tests of the liquid absorbing particles 121, the negative electrode sheet 100 and the battery 200 of Examples 1 to 12 and Comparative Examples 1 to 3:

[0120] 1. Test of the liquid absorption amount of the liquid absorbing particles 121:

[0121] (1) Test of the liquid absorption amount of the liquid-absorbing particles 121 of Example 1 and Comparative Example 1:

[0122] At room temperature, two glass test tubes are prepared, and 5 ml of electrolyte 230 is added to both glass test tubes. The liquid-absorbing particles 121 of Example 1 and Comparative Example 1 are added to different test tubes respectively until there is no obvious liquid flow when the test tubes are tilted, and the mass m of the liquid-absorbing particles 121 added to the test tubes is counted. The calculation formula of the liquid absorption amount Q of the liquid-absorbing particles 121 is: Q=5 ml / m, that is, the value of the liquid absorption amount Q of the liquid-absorbing particles 121 is the ratio of 5 ml to the mass m of the liquid-absorbing particles 121 added to the test tubes. The values ​​of the liquid absorption amount Q of the liquid-absorbing particles 121 of Example 1 and Comparative Example 1 are shown in Table 2.

[0123] (2) Test of the liquid absorption amount of the liquid-absorbing particles 121 of Example 1 at different temperatures:

[0124] Weigh a certain mass of the liquid-absorbing particles 121 of Example 1, place them in a 60°C oven, a 100°C oven, a 130°C oven, and a 150°C oven, respectively, and mark them as test group 1, test group 2, test group 3, and test group 4, and take them out after keeping them constant for 1 hour. Prepare four glass test tubes, and add 5 ml of electrolyte 230 to each glass test tube, and add the liquid-absorbing particles 121 of test group 1, test group 2, test group 3, and test group 4 to different stripping test tubes until there is no obvious liquid flow when the test tube is tilted. Count the mass of the liquid-absorbing particles 121 added to the test tube to obtain the liquid absorption amount of the liquid-absorbing particles 121 of Example 2 at different temperatures. The values ​​of the liquid absorption amount Q of the liquid-absorbing particles 121 of Example 2 at different temperatures are shown in Table 3.

[0125] The calculation method of the liquid absorption amount Q of the liquid absorbing particles 121 is as described above and will not be repeated here.

[0126] (3) Test of liquid absorption amount of the liquid-absorbing particles 121 of Comparative Example 3 and Examples 7 to 12:

[0127] A certain mass of the liquid-absorbing particles 121 of Comparative Example 3 and Examples 7 to 12 was weighed, placed in an oven at 130°C, and kept constant for 1 hour before being taken out. Seven glass test tubes were prepared, and 5 ml of electrolyte 230 was added to each glass test tube, and the liquid-absorbing particles 121 of Comparative Example 3 and Examples 7 to 12 were added to different stripping test tubes respectively until no obvious liquid flowed when the test tube was tilted, and the mass of the liquid-absorbing particles 121 added to each test tube was counted to obtain the liquid absorption amount of the liquid-absorbing particles 121 of Comparative Example 3 and Examples 7 to 12 at 130°C. The value of the liquid absorption amount Q of the liquid-absorbing particles 121 of Comparative Example 3 and Examples 7 to 12 is shown in Table 4.

[0128] 2. Liquid absorption test of negative electrode sheet 100:

[0129] (1) Test of the liquid absorption amount of the negative electrode sheet 100 of Examples 1 to 6 and Comparative Example 2:

[0130] The negative electrode sheets 100 of Examples 1 to 6 and Comparative Example 2 are cut to have a size of 2 cm×2 cm and an area of ​​4 cm 2 , placed in an oven at 130°C, kept constant for 1 hour and then taken out. Prepare seven glass test tubes, place the negative electrode sheets 100 of Examples 1 to 6 and Comparative Example 2 in the glass test tubes, add electrolyte 230 to the seven glass test tubes respectively, until the negative electrode sheets 100 can no longer absorb the electrolyte 230, count the amount V of electrolyte 230 added to each test tube, to obtain the liquid absorption amount of the negative electrode sheets 100 of Examples 1 to 6 and Comparative Example 2 at 130°C, and the value of the liquid absorption amount Q' of the negative electrode sheets 100 of Examples 1 to 6 and Comparative Example 2 is shown in Table 5.

[0131] The calculation formula of the liquid absorption amount Q' of the negative electrode plate 100 is: Q'=V / 4cm 2 , that is, the value of the liquid absorption amount Q' of the negative electrode plate 100 is the amount V of the electrolyte 230 added to the test tube and 4cm 2 ratio.

[0132] (2) Test of the liquid absorption of the negative electrode sheets 100 of Example 2, Example 1 and Example 5 at different temperatures:

[0133] The negative electrode sheet 100 of Example 2 is cut to have a size of 2 cm×2 cm and an area of ​​4 cm 2, the number of cut slices is five, which are placed in a 60°C oven, a 100°C oven, a 130°C oven, a 150°C oven, and a 180°C oven, respectively, and are marked as test group 5, test group 6, test group 7, test group 8, and test group 9, and taken out after being kept constant for 1 hour. Five glass test tubes are prepared, and the negative electrode sheets 100 of test group 5, test group 6, test group 7, test group 8, and test group 9 are placed in the glass test tubes, and electrolyte 230 is added to the five glass test tubes respectively until the negative electrode sheet 100 can no longer absorb the electrolyte 230. The amount of electrolyte 230 added to each test tube is counted to obtain the liquid absorption of the negative electrode sheet 100 of test group 5, test group 6, test group 7, test group 8, and test group 9. The value of the liquid absorption Q' of the negative electrode sheet 100 of Example 2 at different temperatures is shown in Table 6.

[0134] The negative electrode sheet 100 of Example 1 is cut to have a size of 2 cm×2 cm and an area of ​​4 cm 2 , the number of cut slices is five, which are placed in a 60°C oven, a 100°C oven, a 130°C oven, a 150°C oven, and a 180°C oven, respectively, and are marked as test group 15, test group 16, test group 17, test group 18, and test group 19, and taken out after being kept constant for 1 hour. Five glass test tubes are prepared, and the negative electrode sheets 100 of test group 15, test group 16, test group 17, test group 18, and test group 19 are placed in the glass test tubes, and electrolyte 230 is added to the five glass test tubes respectively until the negative electrode sheet 100 can no longer absorb the electrolyte 230. The amount of electrolyte 230 added to each test tube is counted to obtain the liquid absorption of the negative electrode sheet 100 of test group 15, test group 16, test group 17, test group 18, and test group 19. The value of the liquid absorption Q' of the negative electrode sheet 100 of Example 1 at different temperatures is shown in Table 6.

[0135] The negative electrode sheet 100 of Example 5 is cut to have a size of 2 cm×2 cm and an area of ​​4 cm 2 , the number of cut slices is five, which are placed in a 60°C oven, a 100°C oven, a 130°C oven, a 150°C oven, and a 180°C oven, respectively, and are marked as test group 15, test group 16, test group 17, test group 18, and test group 19, and taken out after being kept constant for 1 hour. Five glass test tubes are prepared, and the negative electrode sheets 100 of test group 15, test group 16, test group 17, test group 18, and test group 19 are placed in the glass test tubes, and electrolyte 230 is added to the five glass test tubes respectively until the negative electrode sheet 100 can no longer absorb the electrolyte 230. The amount of electrolyte 230 added to each test tube is counted to obtain the liquid absorption of the negative electrode sheet 100 of test group 15, test group 16, test group 17, test group 18, and test group 19. The value of the liquid absorption Q' of the negative electrode sheet 100 of Example 5 at different temperatures is shown in Table 6.

[0136] The calculation method of the liquid absorption amount Q' of the negative electrode plate 100 is as described above and will not be repeated here.

[0137] 3. Performance test of battery 200:

[0138] The implementation battery 1 and the comparison battery 2 were tested: the fully charged implementation battery 1 and the comparison battery 2 were overcharged at a constant current of 0.25C until the voltage reached 1.5 times of the rated maximum voltage, and then left to stand for 1 hour for observation. The curves of the voltage and temperature of the implementation battery 1 and the comparison battery 2 changing with time are shown in FIG. Figure 4 shown.

[0139] Table 2: Performance parameters of the liquid-absorbing particles 121 of Example 1 and Comparative Example 1.

[0140] Examples and Comparative Examples Liquid absorption of liquid-absorbing particles Q (mL / g) Example 1 15.15 Comparative Example 1 25

[0141] Table 3: Performance parameters of the liquid-absorbing particles 121 of Example 1 at different temperatures.

[0142]

[0143] Table 4: Performance parameters of the liquid-absorbing particles 121 of Comparative Example 3 and Examples 7 to 12.

[0144] Examples and Comparative Examples Liquid absorption of liquid-absorbing particles Q (mL / g) Example 7 7.58 Example 8 8.77 Example 9 12.2 Example 10 15.63 Embodiment 11 17.24 Example 12 20 Comparative Example 3 5.56

[0145] Table 5: Performance parameters of the negative electrode sheets 100 of Examples 1 to 6 and Comparative Example 2.

[0146] Examples and Comparative Examples Liquid absorption of liquid-absorbing particles Q (mL / g) Example 1 0.875 Example 2 1.05 Example 3 1.25 Example 4 1.4 Example 5 1.575 Example 6 1.563 Comparative Example 2 0.75

[0147] Table 6: Performance parameters of the negative electrode sheets 100 of Example 2, Example 1 and Example 5 at different temperatures.

[0148]

[0149]

[0150] As can be seen from Table 1 and Table 2, the negative electrode plate 100 of Example 1 includes liquid-absorbing particles 121, and the liquid-absorbing particles 121 include a liquid-absorbing core layer 1211 and a shell 1212, and the median particle size of the liquid-absorbing core layer 1211 and the thickness of the shell 1212 are both within a reasonable range. Although the liquid-absorbing particles 121 of Comparative Example 1 include a liquid-absorbing core layer 1211, no shell 1212 is provided on the periphery of the liquid-absorbing core layer 1211. In the test of Example 1 and Comparative Example 1, the liquid absorption amount of the liquid-absorbing particles 121 is tested under normal temperature conditions. As can be seen from the data in Table 2, the liquid absorption amount of the liquid-absorbing particles 121 of Comparative Example 1 is 25 mL / g, and the liquid absorption amount of the liquid-absorbing particles 121 of Example 1 is 15.15 mL / g, that is, the liquid absorption amount of the liquid-absorbing particles 121 of Comparative Example 1 is greater than the liquid absorption amount of the liquid-absorbing particles 121 of Example 1. This is because: Comparative Example 1 directly measures the adsorption of the electrolyte 230 by the liquid absorbing core layer 1211, while the outer periphery of the liquid absorbing core layer 1211 of Example 1 is provided with a shell 1212, and the shell 1212 prevents the liquid absorbing core layer 1211 from adsorbing the electrolyte 230 without melting, so that when the battery 200 is in normal working state, the shell 1212 can protect the liquid absorbing core layer 1211 to prevent the liquid absorbing core layer 1211 from absorbing liquid and causing polarization of the battery 200, thereby making the battery 200 have better cycle performance.

[0151] As can be seen from Table 1 and Table 3, the liquid absorbing particles 121 of Example 1 are placed in a 60°C oven, a 100°C oven, a 130°C oven, and a 150°C oven, respectively, to simulate the ambient temperature of the liquid absorbing particles 121 when the liquid absorbing particles 121 are applied to the negative electrode sheet 100 and assembled in the battery 200, that is, to simulate the temperature inside the battery 200. As can be seen from the data in Table 3, as the temperature of the environment in which the liquid absorbing particles 121 are located increases, the amount of liquid absorbed by the liquid absorbing particles 121 gradually increases first and then tends to be flat, because: as the temperature of the environment in which the liquid absorbing particles 121 are located increases, the outer shell 1212 of the liquid absorbing particles 121 gradually melts, and the liquid absorbing core layer 1211 is exposed, so as to increase the contact area between the liquid absorbing core layer 1211 and the electrolyte 230, and then increase the amount of the liquid absorbing particles 121 adsorbing the electrolyte 230. However, when the temperature of the environment in which the liquid-absorbing particles 121 are located rises to a certain value, the liquid-absorbing performance of the liquid-absorbing core layer 1211 is difficult to continue to improve due to limitations of specific surface area, median particle size, etc.

[0152] It can be seen from Table 1 and Table 4 that the liquid-absorbing particles 121 of Comparative Example 3 and Examples 7 to 12 are placed in an oven at 130°C and kept constant for 1 hour before being taken out. At this time, the outer shell 1212 of the liquid-absorbing particles 121 melts and the liquid-absorbing core layer 1211 is exposed, and the liquid-absorbing particles 121 can play a liquid-absorbing function. The median particle size of the liquid-absorbing core layer 1211 in Comparative Example 3 is too large, and the median particle size of the liquid-absorbing particles 121 is too large. The median particle size of the liquid-absorbing core layer 1211 of Examples 7 to 12 meets the reasonable range, and the median particle size of the liquid-absorbing core layer 1211 of Examples 7 to 12 gradually decreases, so that the liquid-absorbing amount of the liquid-absorbing particles 121 of Examples 7 to 12 is greater than the liquid-absorbing amount of the liquid-absorbing particles 121 of Comparative Example 3, and as the median particle size of the liquid-absorbing core layer 1211 gradually decreases, the liquid-absorbing amount of the corresponding liquid-absorbing particles 121 gradually increases. This is because: as the median particle size of the liquid absorbing core layer 1211 gradually decreases, the specific surface area of ​​the liquid absorbing core layer 1211 gradually increases, so that when the shell 1212 melts and the liquid absorbing core layer 1211 is exposed, there is a larger contact area between the liquid absorbing core layer 1211 and the electrolyte 230, and the liquid absorbing core layer 1211 can quickly contact and absorb a large amount of electrolyte 230, so as to intensify the polarization phenomenon of the battery 200, so that the battery 200 quickly reaches the cut-off voltage, so as to improve the safety performance of the battery 200 in an overcharge state.

[0153] It can be seen from Table 1 and Table 5 that the negative electrode sheets 100 of Examples 1 to 6 and Comparative Example 2 are cut and placed in an oven, kept constant for 1 hour and then taken out. At this time, the outer shell 1212 of the liquid absorbing particles 121 melts and the liquid absorbing core layer 1211 is exposed. At this time, the liquid absorbing particles 121 in the negative electrode sheet 100 can play a liquid absorbing function. In the negative electrode material layer 120 of the negative electrode plates 100 of Examples 1 to 6, the mass fraction a of the liquid absorbing particles 121 all meets a reasonable range, while Comparative Example 2 does not include the liquid absorbing particles 121, which makes the liquid absorption amount of the negative electrode plates 100 of Examples 1 to 6 greater than the liquid absorption amount of the negative electrode plates 100 of Comparative Example 2, and as the mass fraction a of the liquid absorbing particles 121 increases, the liquid absorption amount of the negative electrode plates 100 generally shows an increasing trend. This is because: as the mass fraction a of the liquid absorbing particles 121 gradually increases, the greater the mass proportion of the liquid absorbing particles 121 in the negative electrode material layer 120, when the battery 200 is in an overcharge state 1, the outer shell 1212 of the liquid absorbing particles 121 melts and the liquid absorbing core layer 1211 is exposed, and the more liquid absorbing particles 121 there are, the more electrolyte 230 can be quickly absorbed, thereby increasing the liquid absorption amount of the negative electrode plates 100 in turn.

[0154] It can be understood that the liquid absorption amount Q' of the negative electrode plate 100 is positively correlated with the liquid absorption amount Q of the corresponding liquid-absorbing particles 121. In other words, when the liquid absorption amount Q of the liquid-absorbing particles 121 is larger, the corresponding liquid absorption amount Q' of the negative electrode plate 100 is larger; when the liquid absorption amount Q of the liquid-absorbing particles 121 is smaller, the corresponding liquid absorption amount Q' of the negative electrode plate 100 is smaller.

[0155] As can be seen from Table 1 and Table 6, the liquid absorption of the negative electrode sheets 100 of Example 2, Example 1 and Example 5 at different temperatures was tested respectively. Specifically, the negative electrode sheet 100 of Example 2 was cut and placed in a 60°C oven, a 100°C oven, a 130°C oven, a 150°C oven and a 180°C oven respectively to simulate the ambient temperature of the negative electrode sheet 100 when the negative electrode sheet 100 was assembled in the battery 200, that is, to simulate the temperature inside the battery 200. As can be seen from the data in Table 6, as the temperature of the environment in which the negative electrode sheet 100 is located increases, the liquid absorption of the negative electrode sheet 100 gradually increases. This is because: as the temperature of the environment in which the negative electrode sheet 100 is located increases, the outer shell 1212 of the liquid absorbing particles 121 in the negative electrode sheet 100 gradually melts to expose the liquid absorbing core layer 1211 and adsorb the electrolyte 230 to increase the liquid absorption of the negative electrode sheet 100. Similarly, the negative electrode sheets 100 of Example 1 were cut and placed in ovens at 60°C, 100°C, 130°C, 150°C, and 180°C, respectively, and the liquid absorption of the negative electrode sheets 100 of test groups 10 to 14 gradually increased; the negative electrode sheets 100 of Example 5 were cut and placed in ovens at 60°C, 100°C, 130°C, 150°C, and 180°C, respectively, and the liquid absorption of the negative electrode sheets 100 of test groups 15 to 19 gradually increased and then tended to be flat.

[0156] Further, please refer to test group 5, test group 10 and test group 15. At the same temperature, the liquid absorption amount of the negative electrode sheet 100 of test group 5, test group 10 and test group 15 gradually increases. This is because: the mass fraction of the liquid absorption particles 121 of the negative electrode sheet 100 of test group 5, test group 10 and test group 15 gradually increases to improve the liquid absorption effect of the negative electrode sheet 100. Similarly, please refer to test group 6, test group 11 and test group 16, test group 7, test group 12 and test group 17, test group 8, test group 13 and test group 18, and test group 9, test group 14 and test group 19, and the same rules can be obtained.

[0157] From Table 1 and Figure 4It can be seen that the implementation battery 1 includes liquid absorbing particles 121 and the mass fraction of the liquid absorbing particles 121, the median particle size of the liquid absorbing core layer 1211, the thickness of the shell 1212, the median particle size of the liquid absorbing particles 121 and the specific surface area of ​​the liquid absorbing core layer 1211 are all within a reasonable range, and the negative electrode material layer 120 of the comparative battery 2 does not include the liquid absorbing particles 121. Figure 4 It can be seen that compared with the comparative battery 2, the implementation battery 1 can quickly obtain the cut-off voltage, and the temperature change of the implementation battery 1 tends to be gentle. This is because: the heat generated by the overcharge device of the battery 200 can make the temperature of the battery 200 close to 150°C, and the shell 1212 of the liquid-absorbing particles 121 in the implementation battery 1 melts to expose the liquid-absorbing core layer 1211, and the liquid-absorbing core layer 1211 absorbs a large amount of electrolyte 230 to intensify the polarization phenomenon of the battery 200, so that the battery 200 quickly reaches the cut-off voltage, thereby shortening the time that the battery 200 is in the overcharge state, and reducing the heat generated by the implementation battery 1 in the overcharge state, so that the temperature of the implementation battery 1 tends to be gentle. On the contrary, the comparative battery 2 has thermal runaway in the static stage. After a certain period of time, the voltage of the comparative battery 2 drops sharply and the temperature rises sharply. This is because the comparative battery 2 does not include the liquid-absorbing particles 121. When the battery 200 is in an overcharged state, the electrolyte 230 inside the battery 200 reacts with the active particles in a large number of side reactions to generate more heat, thereby causing the temperature inside the comparative battery 2 to change sharply, and the overcharge performance of the comparative battery 2 is poor. In summary, the liquid-absorbing particles 121 are added to the negative electrode material layer 120. The liquid-absorbing particles 121 trigger the liquid-absorbing performance when the battery 200 is in an overcharged state and the temperature is high, so as to consume a large amount of electrolyte 230, thereby avoiding the occurrence of thermal runaway and improving the safety performance and cycle performance of the battery 200 in an overcharged state.

[0158] See also Figure 5 and Figure 6 The present application also provides an electrical device 300 , which includes: a device body 310 and a battery 200 provided in the present application, and the battery 200 supplies power to the device body 310 .

[0159] It can be understood that the battery 200 is electrically connected to the device body 310 .

[0160] In this embodiment, the battery 200 has good safety performance and cycle performance in an overcharged state, so that the battery 200 can provide stable power to the device body 310, which is beneficial to improving the user experience.

[0161] Optionally, the power-consuming device 300 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 5 The electrical equipment 300 of the embodiment is an energy storage battery cabinet.

[0162] It can be understood that the electric device 300 described in this embodiment is merely a form of the electric device 300 used by the battery 200, and should not be understood as a limitation on the electric device 300 provided in this application, nor should it be understood as a limitation on the electric device 300 provided in each embodiment of this application.

[0163] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.

[0164] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate includes: a negative electrode current collector layer and a negative electrode material layer, the negative electrode current collector layer and the negative electrode material layer are stacked, the negative electrode material layer includes liquid absorbing particles, the liquid absorbing particles include a liquid absorbing core layer and a shell, the shell is coated on the periphery of the liquid absorbing core layer, the shell is a polymer shell layer, and the melting temperature T of the shell is in the range of: 100°C≤T≤150°C.

2. The negative electrode sheet according to claim 1, characterized in that: The conductivity σ of the shell is in the range of 10 -12 S / m≤σ≤10 -9 S / m.

3. The negative electrode sheet according to claim 1, characterized in that: The range of the liquid absorption amount Q of the liquid absorbing particles per unit mass is: 3 mL / g≤Q≤7 mL / g.

4. The negative electrode sheet according to claim 1, characterized in that: The range of the median particle size d1 of the liquid absorbing core layer is: 10nm≤d1≤500nm.

5. The negative electrode sheet according to claim 1, characterized in that: The specific surface area S of the liquid absorbing core layer is in the range of: 1.1 m 2 / g≤S≤1.7m 2 / g.

6. The negative electrode sheet according to claim 1, characterized in that: The thickness of the shell is h, and the median particle size of the liquid absorbing particles is d2, then the relationship is satisfied: 0.3≤h / d2≤0.

5.

7. The negative electrode sheet according to claim 6, characterized in that: The thickness h of the shell is in the range of 20 nm ≤ h ≤ 300 nm.

8. The negative electrode sheet according to claim 6, characterized in that: The range of the median particle size d2 of the liquid absorbing particles is: 20nm≤d2≤1000nm.

9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: In the negative electrode material layer, the mass fraction a of the liquid absorbing particles is in the range of 0.1%≤a≤0.5%.

10. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The liquid absorbing core layer comprises a silicon-based material, and the silicon-based material comprises at least one of silicon dioxide, silicon, silicon carbide, and sodium silicate.

11. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The material of the shell is selected from at least one of polyethylene, polyacrylic acid, polyimide, polyester, polyvinyl chloride, polyethylene terephthalate and polybutylene succinate.

12. A battery, characterized in that: The battery comprises: The negative electrode sheet according to any one of claims 1 to 11; A diaphragm, the diaphragm being arranged on one side of the negative electrode plate; A positive electrode sheet, the positive electrode sheet being disposed on a side of the diaphragm away from the negative electrode sheet; and An electrolyte is used to soak at least a portion of the negative electrode plate, the separator and the positive electrode plate.

13. An electrical equipment, characterized in that: The electrical equipment includes: The device itself; and The battery of claim 12, wherein the battery is used to power the device body.

Citation Information

Cited By

  • Negative pole piece, battery and electric equipment

    CN120015771A

  • Negative electrode sheet, battery and electrical equipment

    CN120015771B